2017
DOI: 10.1002/1873-3468.12796
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of rhomboid‐like pseudoproteases in inflammatory and innate immune responses

Abstract: Edited by Wilhelm JustRhomboid-like pseudoproteases are a conserved superfamily of proteins related to the rhomboid intramembrane serine proteases that lack key catalytic residues. iRhom2, a member of the rhomboid-like pseudoprotease superfamily, regulates the maturation and trafficking of ADAM17 and is associated with inflammatory arthritis. Recent studies demonstrate that iRhom2 is also involved in innate immunity by regulating the trafficking and stability of MITA (also called STING), which is a central ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
(137 reference statements)
0
7
0
Order By: Relevance
“…We hypothesize that CspC (functioning as the bile acid germinant receptor) and CspA (functioning as the amino acid co-germinant receptor) inhibit CspB activity within dormant spores (Fig 8A). These two pseudoproteases would regulate the activity of CspB so that it does not prematurely activate proSleC, potentially similar to how other pseudoproteases / pseudokinases regulate activity of their cognate proteins [6064]. Should proSleC become activated prematurely, the C .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that CspC (functioning as the bile acid germinant receptor) and CspA (functioning as the amino acid co-germinant receptor) inhibit CspB activity within dormant spores (Fig 8A). These two pseudoproteases would regulate the activity of CspB so that it does not prematurely activate proSleC, potentially similar to how other pseudoproteases / pseudokinases regulate activity of their cognate proteins [6064]. Should proSleC become activated prematurely, the C .…”
Section: Discussionmentioning
confidence: 99%
“…g ., Caulobacter crescentus DivL [65] or Streptococcus pyogenes RocA [66]] and eukaryotes [6063] where they often regulate their cognate protease / kinase. Pseudoproteases, however, have mostly been studied in eukaryotes [64]. Prior work by Hershey and colleagues [67] has revealed that Magnetospirillum magneticum uses a pseudoprotease, MamO, to bind metals for magnetosome development.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the loss of their characteristic enzymatic activity, pseudoenzymes have emerged as important proteins that act as allosteric regulators of active enzymes 22 , signal integrators 23,24 and as regulators of protein trafficking 25 . Most biochemical studies of pseudoenzymes have been carried out in Drosophila or mammals 2628 . In this study, we characterized a novel pseudo-aspartic peptidase from the tick R .…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that CspC (functioning as the bile acid germinant receptor) and CspA (functioning as the amino acid co-germinant receptor) inhibit CspB activity within dormant spores (Figure 8). These two pseudoproteases would regulate the activity of CspB so that it does not prematurely activate proSleC, potentially similar to how other pseudoproteases / pseudokinases regulate activity of their cognate proteins [5559]. Because yabG mutant spores package full length CspBA, where CspA is tethered to CspB, CspC alone prevents CspB from cleaving proSleC into its active form, and TA might dislodge CspC from CspB (this is consistent with our prior publication that indicates that CspC may have an inhibitory activity during spore germination [33]).…”
Section: Discussionmentioning
confidence: 99%